Multi-factor authentication as an IT security measure against cyber threats: An approach to be adopted by African countries and companies - (:unkn) unknown (My University, 2024)
Since the digital world has invaded planet Earth and since man has been able to communicate remotely with his neighbor on the other side of the world, man has become vulnerable.Since companies seek to increase their productivity and potential new customers online, and to house all the information relating to the company including these agents, on the servers, it becomes vulnerable.In the African continent, the notion of computer security often poses a problem or even its popularization is not yet widespread in some countries and in most of these countries the frequency of computer threats is booming. The African population suffers from the problem of digital extortion, online scams and so many other cyber threats every day.Every year, nearly 90% of African companies are threatened by cyberattacks because these companies' IT security is not really up to par.Few agents of African businesses, schools, universities and governments are aware in the area of cyberattack or cyberthreat. This paves the way for cyberattacks to threaten and defraud people while stealing user data. It is advised that the protection of user data is of paramount priority for a company and multi-factor authentication constitutes one of the safest ways to verify the identity of customers, agents when they log into a company system or website. In this article, we will present to you the importance of multi-factor authentication to secure remote access and strengthen security and reduce the risks of attacks and theft of user information in an information system of a business.
Keywords: African Research